Analyse of students' assessment during final exams in secondary school and their first and second sessions in mathematics at Vytautas Magnus University and Kaunas Technical College - Rutkienė, Aušra; Augutienė, Elvyra (Lietuvos matematikos rinkinys, 2005)
The analysis of the of students’ assessment during final exams in secondary school and their first and second sessions at college and at university in mathematics was presented. Analysis demonstrates that  students are not ready to work hard in case to get better marks at college and university. The students' grades are decreasing; but there is correlation between school grade and university's or college’s grade.
Keywords: final exams in secondary school; session exams; correlation between school grade and university/ college grade